(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The possible hepatoprotective effects of polyherbal mixes have attracted a lot of interest, but there hasn’t been a tonne of study into their phytochemical profiles or effectiveness. Using a fresh perspective, this study will investigate the phytochemical components and hepatoprotective benefits of several polyherbal formulations. The purpose of this study is to examine polyherbal combinations from a phytochemical perspective and assess their potential for hepatoprotection in animal models. For this investigation, we used three different polyherbal blends: Livina (A), Livotone (C), and Livad (B). The presence of important bioactive chemicals such as sterols, flavonoids, alkaloids, and tannins was determined using phytochemical profiling, which included the use of conventional screening techniques. In a rat model of CCl4-induced liver damage, hepatoprotective effectiveness was evaluated using measures such as antioxidant enzyme activities, histological examination, and liver enzyme levels. All of the formulations had high concentrations of tannins, alkaloids, and flavonoids, although the amounts of sterols varied. Lower blood liver enzyme levels and better liver histology were signs that all three formulations provided significant protection against CCl4-induced liver damage in the hepatoprotective study. Antioxidant tests provided further evidence that the formulations might mitigate the oxidative stress caused by liver injury. The research confirms the hepatoprotective efficacy of chosen polyherbal mixes by effectively profiling their phytochemical ingredients. These results provide credence to the formulations’ long history of usage and demonstrate their potential as powerful therapies in the fight against liver damage. The therapeutic effectiveness and safety of these formulations should be further established via clinical studies, and future research should aim to standardise them.